2014
DOI: 10.5301/ru.2014.11986
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Contrast-Enhanced Ultrasound Scan (CEUS) and MRI in the follow-up of cryoablation for small renal tumors. Experience on 25 cases

Abstract: CEUS is effective during the follow-up of renal tumor cryoablation. It could be an alternative technique to standard CT and MRI, with some advantages: low cost, short time consuming procedure, no radiation exposure, reduced amount of contrast agent (1-2 mL) and rare adverse reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
0
7
0
2
Order By: Relevance
“…There is no relevant literature regarding the use of contrast-enhanced US (CEUS) in the follow-up of patients after surgical excision of RCC, and this method is not included in the guidelines [2,6,7]. However, data from studies evaluating the performance of CEUS after ablative treatment of renal masses demonstrated that CEUS had an excellent concordance with CT or MRI with regard to the presence or absence of residual or recurrent tumor after ablation, both immediately after treatment and through long-term follow-up [28][29][30][31][32][33]. One important consideration is that CEUS would still be less sensitive than CT or MRI for the detection of distant visceral and nodal metastases since the contrast-enhanced portion of the study would be limited to the surgical bed.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no relevant literature regarding the use of contrast-enhanced US (CEUS) in the follow-up of patients after surgical excision of RCC, and this method is not included in the guidelines [2,6,7]. However, data from studies evaluating the performance of CEUS after ablative treatment of renal masses demonstrated that CEUS had an excellent concordance with CT or MRI with regard to the presence or absence of residual or recurrent tumor after ablation, both immediately after treatment and through long-term follow-up [28][29][30][31][32][33]. One important consideration is that CEUS would still be less sensitive than CT or MRI for the detection of distant visceral and nodal metastases since the contrast-enhanced portion of the study would be limited to the surgical bed.…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
“…US Abdomen with IV Contrast. The use of CEUS after radiofrequency ablation, microwave ablation, and cryoablation of renal masses has been the subject of several studies [28][29][30][31][32][33]. In all of these studies, CEUS had an excellent concordance with CT or MRI with regard to the presence or absence of enhancement in renal masses after ablation, both immediately after treatment and through long-term follow-up.…”
Section: Variant 2: Follow-up For Clinically Localized Renal Cell Canmentioning
confidence: 99%
“…Сейчас на основе этих данных можно отметить, что контрастный препарат дает возможность визуализировать микроциркуляцию крови в паренхиме, пирамидках, сосудах почечного синуса и в очаговых образованиях почек. Исследования применения соновью при почечных заболеваниях показали его высокую эффективность, выражающуюся в быстроте выполнения исследования, степени его информативности, отсутствии лучевой нагрузки и нежелательных аллергических реакций [43,44,48,49,[53][54][55]. Рядом исследователей были предприняты попытки применения этой методики для дифференциальной диагностики между разными гистологическими типами почечно-клеточного рака [43][44][45][46].…”
Section: Use Of the Contrast Agent In The Ultrasound Diagnosis Of Kidunclassified
“…Zeccolini и соавт. [43] провели исследование, в котором оценили результаты использования УЗ-контрастирования в диагностике после проведенной криоабляции с помощью УЗИ и МРТ с контрастированием. УЗИ с контрастированием использовали у 25 пациентов.…”
Section: Use Of the Contrast Agent In The Ultrasound Diagnosis Of Kidunclassified
“…Modern cryoablation, in which tumor tissue destructions are achieved by the ultra-low temperature, has been performed in management of solid tumors for more than two decades [20,46]. In contrast to those aggressive tumor-damaging approaches such as surgical excision, chemotherapy or radiation, cryotherapy may be an alternative or even a superior means.…”
Section: Introductionmentioning
confidence: 99%